University Students' Lifestyle in the Context of Physical Activity, Sedentary Habits, and Academic Achievements - Prskalo, Ivan; Planinšec, Jurij (Revija za elementarno izobraževanje, 2025)
This study aims to explore the relationship between physical activity, sedentary behaviour, and academic achievement among university students. A total of 243 students aged 18 to 24 years participated. Physical activity was assessed using the International Physical Activity Questionnaire – Short Form, while sedentary behaviour was measured with the SIT-Q-7d. Academic achievement was based on self-reported average grades and compared across physical activity levels using one-way ANOVA. Results indicate that higher physical activity is not necessarily linked to better academic performance. Excessive involvement in physical activity may reduce study time, potentially leading to lower academic outcomes.
Keywords: physical activity, sedentary behaviour, academic achievement, university students, cognitive performance.